2015
DOI: 10.3109/14767058.2015.1095880
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of mirror syndrome: a comparison of 10 cases of mirror syndrome with non-mirror syndrome fetal hydrops cases

Abstract: Mirror syndrome is occurred frequently in early and severe fetal hydrops and cause hemodilution and elevation of serum hCG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 10 publications
4
22
2
3
Order By: Relevance
“…PAC can be released by hCG directly via stimulation of the luteinizing hormone receptor expressed in the adrenal gland. 15 Elevated hCG level is seen in Ballantyne syndrome, 2 as was seen in the present case. However, it is unknown whether the elevated hCG level plays a role in the clinical manifestations of Ballantyne syndrome via stimulation of PAC release.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…PAC can be released by hCG directly via stimulation of the luteinizing hormone receptor expressed in the adrenal gland. 15 Elevated hCG level is seen in Ballantyne syndrome, 2 as was seen in the present case. However, it is unknown whether the elevated hCG level plays a role in the clinical manifestations of Ballantyne syndrome via stimulation of PAC release.…”
Section: Discussionsupporting
confidence: 75%
“…Ballantyne syndrome, also called mirror syndrome, is characterized by triple edema, including fetal and placental hydrops and maternal edema. 1,2 Other clinical signs include hypertension (in 57-78% of patients), proteinuria (20-56%), pulmonary edema (21%), and intrauterine fetal death (56%), as described in a previous review by Braun et al 1 Triple edema occurs regardless of the etiology underlying fetal hydrops, including rhesus isoimmunization, twin-twin transfusion syndrome, viral infection and fetal malformations, and fetal or placental tumors. 1 As excessive water retention is a cardinal sign of Ballantyne syndrome and as pulmonary edema with dyspnea can be considered as a sign associated with heart failure, aberrant water metabolism may be involved in the pathogenesis leading to altered cardiac morphology as well as function.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Elevated levels of hCG and sFlt-1 were shown to be associated with Ballantyne syndrome:2 14 15 maternal serum hCG level is significantly higher for hydropic infants with Ballantyne syndrome than those without (453 000 vs 80 000 IU/L, respectively);2 median (range) plasma sFlt-1 level is significantly higher for mothers with Ballantyne syndrome than those without (3974 (3083–10 780) vs 824 (260–4712) pg/mL, respectively);14 and plasma sFlt-1 levels were 11 650 pg/mL in a woman with cytomegalovirus-induced Ballantyne syndrome15 and 14 117 pg/mL in a woman with parvovirus B19-induced fetal and placental hydrops 16. In addition, in the presence of placentomegaly regardless of its aetiology, elevated levels of sFlt-1 were observed in one case with triploidy (karyotype 69, XXY) at GW 14 (2953 pg/mL) and in another case with hydatidiform moles at GW 18 (4865 pg/mL) 17.…”
Section: Discussionmentioning
confidence: 99%
“…Ballantyne syndrome, also called mirror syndrome or triple oedema, is a rare disorder affecting pregnant women with presentation of fetal and placental hydrops and maternal oedema 1 2. A review of 56 reported cases1 has indicated that Ballantyne syndrome can occur in the presence of hydropic fetus regardless of its aetiology.…”
Section: Introductionmentioning
confidence: 99%